2011
DOI: 10.1097/mlr.0b013e318215d0c9
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Telephonic Counseling Plus Walking for Depressed Diabetes Patients

Abstract: Background Patients with diabetes and depression often have self-management needs that require between-visit support. This study evaluated the impact of telephone-delivered cognitive behavioral therapy (CBT) targeting patients’ management of depressive symptoms, physical activity levels, and diabetes-related outcomes. Methods 291 patients with type 2 diabetes and significant depressive symptoms (Beck Depression Inventory scores ≥14)were recruited from a community-university-and VA healthcare system. A manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
303
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(314 citation statements)
references
References 51 publications
(46 reference statements)
6
303
0
5
Order By: Relevance
“…Interventions like telephonic counseling targeted at these patients, 17 patients' proper follow-up by primary care professionals 23 or drug administration when indicated 14 seem to present positive results in the handling of chronic diseases.…”
Section: Referencesmentioning
confidence: 99%
“…Interventions like telephonic counseling targeted at these patients, 17 patients' proper follow-up by primary care professionals 23 or drug administration when indicated 14 seem to present positive results in the handling of chronic diseases.…”
Section: Referencesmentioning
confidence: 99%
“…The use of two raters highlighted the need for clearly defined criteria by which to score each ACFC item. A manual to help guide [41,42] assignment of ratings is provided in Appendix 3. This guide helped to ensure high reliability between raters.…”
Section: Scoring Treatment Fidelitymentioning
confidence: 99%
“…For example, Lin et al and others have previously shown that depression care management has the potential to improve multiple symptom domains. [8][9][10] Further, patient populations with multiple morbidities and depression may be more responsive to general self-management interventions than are populations with no depression and fewer medical conditions. 11,12 Thus, there seems to be little doubt that care management attending to depression and other conditions has the potential to improve several health outcomes for both conditions.…”
Section: Agency For Healthcare Research and Quality (Ahrq)mentioning
confidence: 99%